Formation of porous zinc nanosystems using direct and reverse flows of DC magnetron sputtering - Latyshev, V.M.; Perekrestov, V.I.; Kornyushchenko, A.S.; Zahaiko, I.V. (Functional Materials, 2017)
The work is devoted to comparative analysis of two technological solutions for Zn nanosystems formation which have been implemented on the basis of direct-current magnetron sputtering. In the first case, conventional magnetron sputtering was used and direct flows were deposited on the substrate positioned in the front of a sputterer. In the second case, reverse flows were used and the substrate was located inside the magnetron sputterer. It has been shown experimentally, that the second technological approach gives more reproducible results as compared to the classical one. In addition, usage of the reverse flows leads to significant increase in the nanosystems deposition rates.